Tinjauan Kehidupan Sosial Ekonomi Petani Salak Di Desa Parsalakan Kecamatan Angkola Barat Kabupaten Tapanuli Selatan - Amalia Tamima , Nadira; Putra Kasea Sinaga, Randa (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Indonesia is an agricultural country with fertile agricultural land, so that most of Indonesia's population works in agriculture. The welfare of the farming community is a condition that reflects the living conditions of the community, which can be seen from the standard of living of the community. Welfare can be interpreted as the adequacy to meet their own needs. Needs that increase from year to year make people have to increase their desire to meet household needs, not only the needs for boards, clothing and food but needs such as education, health and other unexpected things later. The type of research conducted is field research which is descriptive in nature, namely describing systematically, factually and accurately regarding the facts, characteristics and relationships between the phenomena studied. Methods of data collection in this study using interviews, observation and documentation. Based on the results of the research and discussion in this study, it can be concluded that not all Zalacca farmers in Parsalakan Village feel deficient in their crops. Not all Zalacca farmers process their Zalacca if the Zalacca produced is not good. Zalacca farmers are able to fulfill their basic needs such as spiritual needs, shelter, food, clothing and health. In addition to the spiritual needs of salak farmers, they are also able to meet their psychological needs, such as education, interaction within the family and interaction with the environment in which they live. Apart from harvesting zalacca, salak farmers also have side jobs such as growing fruits, vegetables, and selling candied zalacca online.